Comparison of xerostomia incidence after three-dimensional conformal radiation therapy and contralateral superficial lobe parotid-sparing intensity-modulated radiotherapy for oropharyngeal and hypopharyngeal cancer. Issue 5 (October 2018) - Kawamoto, Terufumi; Nihei, Keiji; Nakajima, Yujiro; Kito, Satoshi; Sasai, Keisuke; Karasawa, Katsuyuki
Abstract: Objective: In the treatment of head–neck cancer, parotid-sparing intensity-modulated radiotherapy (IMRT) could reduce the incidence of xerostomia. When the parotid glands cannot be sufficiently spared because of the widespread tumor, contralateral superficial lobe parotid-sparing (CSLPS)-IMRT could be used to reduce marginal recurrence, however the success of this approach remains to be determined. The primary purpose of this study was to compare the incidence of xerostomia between three-dimensional conformal radiotherapy (3D-CRT) and CSLPS-IMRT for oropharyngeal and hypopharyngeal cancer. In a second aim, we also compared the clinical efficacy of 3D-CRT and CSLPS-IMRT. Methods: We retrospectively reviewed the medical records of locally advanced oropharyngeal and hypopharyngeal cancer patients who were treated with definitive concurrent chemoradiotherapy between June 2007 and April 2014. We estimated the average mean dose delivered to the parotid glands, the incidence of xerostomia ≥ Grade 2, patterns of failure, and survival outcomes. Results: Seventeen patients received 3D-CRT and 21 received CSLPS-IMRT. The average mean dose delivered to the superficial lobe of the contralateral parotid gland was 45.3 Gy and 26.6 Gy (p < 0.001), and the incidence of xerostomia ≥ Grade 2 following treatment was 75% and 26% at 12 months (p = 0.012) and 67% and 18% at 24 months (p = 0.018) in the 3D-CRT and CSLPS-IMRT groups, respectively. Patterns of failure did not differ between the two groups. The 2-year progression-free survival was 59% and 62% (p = 0.73), and the 2-year overall survival rate was 71% and 71% in the 3D-CRT and CSLPS-IMRT groups, respectively (p = 0.76). Conclusion: Incidence of xerostomia was significantly lower in patients receiving CSLPS-IMRT compared with 3D-CRT, while clinical efficacy did not differ between two treatment strategies.